Efforts To Increase Student Learning Motivation From A Psychological Perspective - Afifah; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education involves identifying the factors that influence students' learning motivation and assessing the steps that can be taken to improve it. The research method applied is the literature method, where information is collected from various literature sources such as books, scientific reports and journal articles. Desk research was used to gather relevant information from various sources to support the analysis of the concept of learning motivation. The results show that student learning motivation is dynamic and can fluctuate. Therefore, efforts are needed to maintain and increase students' learning motivation. Factors such as ambition, ability, physical and mental conditions, and the learning environment can affect students' learning motivation. Increasing learning motivation can be achieved by stimulating student interest, providing realistic expectations, providing incentives and guiding student behaviour.